The Orthostatic Hypotension Questionnaire in Swedish tested in patients with parkinsonism. Issue 9 (7th July 2020) - Olsson, Andreas; Olsson, Mia; Fedorowski, Artur; Hagell, Peter; Wictorin, Klas
Abstract: Background: Orthostatic hypotension (OH) is common among older people and in particular in conditions like Parkinson's disease (PD). The OH Questionnaire (OHQ) has been proposed as a useful patient‐reported assessment tool consisting of the OH Symptom Assessment (OHSA), OH Daily Activity Scale (OHDAS), and a composite score. Aims of the Study: To translate the OHQ into Swedish and assess its psychometric properties. Methods: Following forward–backward translation, the Swedish OHQ was field‐tested ( n  = 6) for relevance, comprehensibility, and respondent burden. It was then tested regarding scaling assumptions, targeting, reliability, and construct validity in persons with PD ( n  = 27) and multiple system atrophy ( n  = 2). Results: The Swedish OHQ was considered relevant and easy to use, with a mean completion time of 5.3 min. Scaling assumptions were acceptable for OHSA and OHDAS (corrected item‐total correlations, .30–.67) but not for the total score (.12–.69). Floor/ceiling effects were ≤3.4% and reliability was >.64. Construct validity was supported by expected correlations with the SCOPA‐AUT, RAND‐36, and blood pressure measurements. Conclusions: The Swedish OHQ was well received, and psychometric results suggest that the OHQ (particularly the OHDAS) is a useful tool for OH assessment in parkinsonian disorders. Further testing in larger samples is needed.